Diagnostic delay in psoriatic arthritis: insights from a nationwide multicenter study - DURUÖZ, MEHMET TUNCAY (My University, 2023)
This study aimed to investigate the duration of diagnostic delay in patients with psoriatic arthritis (PsA) and identify potential contributing factors using a comprehensive, population-based approach. Data were obtained from the Turkish League Against Rheumatism (TLAR)-Network, involving patients who met the CASPAR criteria. Diagnostic delay was defined as time interval from symptom onset to PsA diagnosis, categorized as ≤ 2 years and > 2 years. Temporal trends were assessed by grouping patients based on the year of diagnosis. Various factors including demographics, clinical characteristics, disease activity, quality of life, physical function, disability, fatigue, and well-being were examined. Logistic regression models were used to identify factors associated with diagnostic delay. Among 1,134 PsA patients, mean diagnostic delay was 35.1 months (median: 12). Approximately 39.15% were diagnosed within 3 months, and 67.02% were diagnosed within 24 months. Patients experiencing longer delays had higher scores in Psoriatic Arthritis Quality of Life Questionnaire (PsAQoL), Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-Fatigue), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), patient’s global assessment (PtGA) and physician’s global assessment (PhGA). Diagnostic delay has decreased over time, with median delay falling from 60 to 24 months throughout pre-2010 and 2015–2019 terms. Several factors were identified as significant contributors to delayed diagnosis, including lower levels of education (OR = 2.63), arthritis symptoms preceding skin manifestations (OR = 1.72), low back pain at first visit (OR = 1.60), symptom onset age (OR = 0.96), and psoriasis subtype (OR = 0.25). Timely diagnosis of PsA is crucial for effective management and improved outcomes. Despite recent improvements, about one-third of PsA patients still experience delays exceeding 2 years. By identifying influential factors such as education level, arthritis symptoms preceding skin manifestations, initial visit symptoms, age of symptom onset, and psoriasis subtype, healthcare practitioners may create specific techniques to help in early detection and intervention.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; ROMATOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; RHEUMATOLOGY; Romatoloji; İmmünoloji ve Alerji; Rheumatology; Immunology and Allergy; Immunology; Arthritis; Delayed diagnosis; Incidental findings; Psoriatic